Monte-Carlo method application in simulations of electron processes at impacts of atoms with the surface - Гранкин, Михаил Викторович; Каргин, Анатолий Алексеевич (Eastern-European Journal of Enterprise Technologies, 2014)
High-efficient energy accommodation of heterogeneous chemical reaction of hydrogen atom recombination by electron subsystem ZnS, ZnS, CdS-Ag, exposed to ionizing radiation is investigated. It is shown that the effect of ionizing radiation on ZnS, ZnS, CdS-Ag increases the reaction heat accommodation rate on the electronic channel by several orders. A model of the mechanism of the heterogeneous recombination of atoms on ZnS, ZnS, CdS-Ag, with the participation of metastable electronic states, generated by ionizing radiation is developed. Numerical and mathematical simulation of the surface processes using theMonte Carlomethod is performed. It is found that the electron channel of accommodation may be the main channel for the H atoms recombination energy accommodation on the considered samples if they are exposed to ionizing radiation. The regions of activation and relaxation catalysis of the H atoms recombination reaction on the ZnS, ZnS, CdS-Ag are defined. The considered problem of exothermic reaction energy accommodation is of a general nature and carries information about the surface and physicochemical processes on it that is important for the physics and technology of semiconductors, catalysis and plasma chemistry.